The Dilemma of Law Enforcement in Determining Suspects in Online Gambling Site Promotion Cases: A Case Study at the South Sulawesi Regional Police - Muhammad Agung Hidayah; La Ode Husen; Muhammad Azham Ilham (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to identify and analyze the obstacles faced by the police in determining suspects in cases involving the promotion of online gambling sites through information technology. This research employs an empirical legal research method, which examines the application of legal norms based on real conditions in the field. Data were collected through interviews, observations, and a literature review of primary and secondary legal materials. The study was conducted at the Regional Police of South Sulawesi (Polda Sulsel).The results indicate that the legal procedure for determining suspects in online gambling promotion cases at Polda Sulawesi Selatan involves several stages: investigation, inquiry, collection of valid evidence, and witness examination. Once at least two sufficient pieces of evidence are obtained in accordance with the Indonesian Criminal Procedure Code (KUHAP), the investigator formally determines the perpetrator as a suspect. Law enforcement is carried out carefully, as offenders often disguise their digital identities using fake accounts, virtual private networks (VPNs), and proxy servers. The main challenges faced by the police include difficulties in tracing perpetrators’ identities due to digital obfuscation, limited access to encrypted communication data, and the lack of public participation in reporting online gambling promotion activities. These findings highlight the importance of improving investigators’ technical capacity and strengthening inter-agency cooperation, particularly with the Ministry of Communication and Informatics and digital platform providers, to enhance the effectiveness of law enforcement against cybercrime based on information technology.